2019
DOI: 10.1111/neup.12624
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial thrombosed anastomosing hemangioma: Case report

Abstract: An anastomosing hemangioma is a relatively new diagnosis of a benign vascular lesion that is typically found in the genitourinary tract. On imaging, anastomosing hemangiomas have a broad differential diagnosis and can resemble malignant lesions such as angiosarcoma. Here we present a case of a 33‐year‐old male with seizures who on imaging was found to have a presumed recurrent intracranial meningioma. After surgical resection of his lesion, this case was pathologically diagnosed as having anastomosing hemangio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Unfortunately, the studies that have reported tumor capsules did not show imaging findings. Its shape can be roundish or irregular with lobulation [ 18 , 20 ]. Furthermore, the internal density is uneven, and only a few cases have demonstrated the presence of fat or calcification [ 7 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the studies that have reported tumor capsules did not show imaging findings. Its shape can be roundish or irregular with lobulation [ 18 , 20 ]. Furthermore, the internal density is uneven, and only a few cases have demonstrated the presence of fat or calcification [ 7 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our present case showed tumor enlargement during follow-up at a growth rate of 3.6 mm per year. AHs in other sites (soft tissue, kidney, intracranial) exhibited varied growth dynamics, from remaining stable to growing rapidly ( 19 , 20 ). A previous study indicated that almost 40% of conventional hepatic hemangiomas increased in size over time with an overall rate of 0.3–2 mm per year in diameter ( 21 ).…”
Section: Discussionmentioning
confidence: 99%